La Política Pública ENIPLA-PEA y su aplicación mediante el proyecto social “Plan Nacional de Fortalecimiento de la Familia” en el Colegio de Bachillerato “Beatriz Cueva de Ayora” de la ciudad de Loja, periodo 2014 - Cosíos Cartuche, Vanessa Alexandra (2017)
The purpose of this thesis is to know the application of the ENIPLA-PEA Public Policy, in the children of the "Beatriz Cueva de Ayora" Baccalaureate School in the city of Loja, to study the strategy of "National Plan for Strengthening the Family". Complying with the development and presentation provided by the Regulations of Academic Regime of the National University of Loja. Thus, in order to analyze the different problems, four objectives were proposed; The first one was studied through three groups of variables that built the level of quality of education provided by teachers in the school, the reception of information about sexual and reproductive education, knowledge of the laws to clarify their duties and rights, as well as The obligations of children and adolescents. The second objective was the effectiveness of health services, taking into account that the school only provides advice on sexual health provided in the different sub centers, centers and hospitals of the Ministry of Public Health. Cultural, moral and economic barriers are factors that prevent the national strategy from being properly applied, so it was established as the third study objective, and finally an improvement plan is proposed in the high school "Beatriz Cueva of Ayora”. All this was done thanks to qualitative and quantitative information, obtained from the application of interviews, surveys and focal analysis, to the beneficiaries and responsible for the implementation and development of the national strategy: Family Strengthening Plan